A rare case of posterior interosseous nerve palsy post-venepuncture - Yeak, Raymond Dieu Kiat; Yee, Yee Yap; Mohd Nasir, Mohd Nizlan (College of Physicians and Surgeons Pakistan, 2021)
Wrist drop post-venepuncture is uncommon. There has been reported cases of direct injury to the radial nerve during venepuncture but to our knowledge, there has never been a case of posterior interosseous nerve (PIN) injury. A 34-year female, right hand dominant homemaker, with a newly diagnosed diabetes mellitus, was admitted for diabetic ketoacidosis. There was difficult access with multiple attempts in her blood taking over the antebrachial fossa and forearm. Thereafter, she was unable to fully extend her wrist, fingers and thumb with an intact sensation. The electrophysiological study was suggestive of demyelinating right radial neuropathy at the elbow. Despite the transient blood taking session, patient developed neuropraxia, which only resolved after four months. We wish to report this case of unusual presentation of a PIN palsy post- routine venepuncture, which can result in high morbidity to a patient. Key Words: Posterior interosseous nerve syndrome, venepuncture, neuropraxia, wrist drop.